The New Encyclopedia of Southern Culture : Volume 4: Myth, Manners, and Memory - Abadie, Ann J.; Thomas, James G., Jr; Wilson, Charles Reagan (Book collections on Project MUSE., 2006)
This volume of The New Encyclopedia of Southern Culture addresses the cultural, social, and intellectual terrain of myth, manners, and historical memory in the American South. Evaluating how a distinct southern identity has been created, recreated, and performed through memories that blur the line between fact and fiction, this volume paints a broad, multihued picture of the region seen through the lenses of belief and cultural practice.